2017
DOI: 10.3389/fimmu.2017.00066
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Associated Lymphatic Vessels Upregulate PDL1 to Inhibit T-Cell Activation

Abstract: Tumor-associated lymphatic vessels (LVs) play multiple roles during tumor progression, including promotion of metastasis and regulation of antitumor immune responses by delivering antigen from the tumor bed to draining lymph nodes (LNs). Under steady-state conditions, LN resident lymphatic endothelial cells (LECs) have been found to maintain peripheral tolerance by directly inhibiting autoreactive T-cells. Similarly, tumor-associated lymphatic endothelium has been suggested to reduce antitumor T-cell responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
100
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 35 publications
1
100
0
Order By: Relevance
“…Our results are striking in terms of the strong inflammatory gene expression signature of 4T1‐associated LECs, which included induction of many chemokines and adhesion molecules. We also found a trend (log 2 FC = 1.96, FDR = 0.68) toward increased expression of the T cell inhibitory protein PD‐L1, which is in line with our own previous observations . Clearly, this proinflammatory gene expression signature is likely to have a plethora of effects on tumor progression, metastasis and host immunity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are striking in terms of the strong inflammatory gene expression signature of 4T1‐associated LECs, which included induction of many chemokines and adhesion molecules. We also found a trend (log 2 FC = 1.96, FDR = 0.68) toward increased expression of the T cell inhibitory protein PD‐L1, which is in line with our own previous observations . Clearly, this proinflammatory gene expression signature is likely to have a plethora of effects on tumor progression, metastasis and host immunity.…”
Section: Discussionsupporting
confidence: 91%
“…Cell suspensions of control skin, 4T1 tumors and tumor‐draining LNs were prepared as described . For staining, the following antibodies were used: CD45‐APC/Cy7 or CD45‐PacificBlue (Biolegend 103116, 103126), CD31‐APC (BD 551262), podoplanin‐PE (eBioscience, San Diego, CA, 12‐5381‐82), CD3‐PE/Cy7 (Biolegend 100220), CD11b‐BV605 (Biolegend 101257), Ly6C‐PE (Biolegend 128008), Ly6G‐FITC (Biolegend 127606), F4/80‐Alexa647 (BioRad MCA497G), VE‐cadherin‐APC (Biolegend 138012) and goat antimouse VCAM‐1 (R&D AF643), followed by washing and labeling with a secondary donkey antigoat‐Alexa488 antibody.…”
Section: Methodsmentioning
confidence: 99%
“…In a murine model of lymphatic-enriched melanoma, we have found that VEGF-Cstimulated LECs in the tdLNs tolerize antitumor CD8 + T cells through cross-presentation of tumor Ags [182]. Very recently, PD-L1 expression by LECs was shown to have a crucial role in the inhibition of CD8 + T cell response in the context of tumor [220]. These studies underline the ability of LECs to extend their Ag presentation abilities beyond PTAs, therefore broadening their role as an active player in immune responses.…”
Section: Antigen Presentation To Cd8 + T Cellsmentioning
confidence: 99%
“…An increase in VEGF‐C expression in tumors is highly correlated with LN metastasis and poor prognosis in individuals with different tumor types, including skin, breast and lung cancers . Furthermore, LEC not only present antigens and modulate immune cell activation in physiology conditions but also promote tumor progression and metastasis by inhibiting the function of immune cells (Figure ) . Mechanistically, VEGF‐C plays an immunosuppressive role for LEC to scavenge and cross‐present antigens for direct suppression of cytotoxic T lymphocytes .…”
Section: Functional Heterogeneity Of Tumor Lymphangiogenesismentioning
confidence: 99%
“…2 Furthermore, LEC not only present antigens and modulate immune cell activation in physiology conditions 64,65 but also promote tumor progression and metastasis by inhibiting the function of immune cells (Figure 3). 40,66 Mechanistically, VEGF-C plays an immunosuppressive role for LEC to scavenge and cross-present antigens for direct suppression of cytotoxic T lymphocytes. 61 LEC can also express immunosuppressive factors such as TGF-β and nitric oxide to maintain peripheral tolerance to self-antigens in lymph nodes by directly or indirectly regulating T-cell fate and function in immunity.…”
Section: Paradoxical Roles In Antitumor Immune Responsementioning
confidence: 99%